Finite element simulation of polygonal rectangular square composite cotton reinforced polyester composites / Akbar Othman and Al Emran Ismail - Othman, Akbar; Ismail, Al Emran (2012)
In this paper the collapse behaviors of composite cotton fiber reinforced polyester were developed and analyzed. The crush studies with various regular polygonal cross-sections were numerically investigated under axial compression using the finite element method program code of LS-DY@A version 3.71. The effects of wall thickness and velocity rate of impact on the crush behavior were also investigated. Crush strength increases as the number of corners of the cross-section increases, though it was almost saturated for the number of corners beyond 10. Cross-sectional shapes with less than five corners should be avoided to take a regulated collapse pattern. The effect of number of polygonal corners on enhancement in crush strength becomes more prominent as the initial wall thickness decreases. The validation finite element modeling was carried out with experimental analysis technique to ensure that the data results from numerical analysis will provide sufficient accuracy.